Screen exposure in Chilean children during early childhood and socio-emotional problems: relationship and directionality - Soto-Ramirez, Pamela; Godoy, Felipe; Narea, Marigen; Ayala, Camila (Frontiers in Psychology, 2025)
IntroductionResearch has found a correlation between screen exposure in early childhood and children’s socio-emotional development, particularly in Global North countries. However, the direction of the effect has not been extensively studied in early childhood, especially in Global South contexts. This study aims to describe the relationship and the bidirectional longitudinal associations between screen exposure and children’s internalizing and externalizing problems among children in Chile.MethodsUsing the Child Behavior Checklist (CBCL), 669 Chilean children were measured two times over a two-year period: in 2021 (T1; mean age = 3.5 years) and 2023 (T2; mean age = 5.4 years). Linear regression analyses were employed to examine the relationship between screen exposure and internalizing and externalizing problems at T1 and T2 separately. A cross-lagged panel model (CLMP) was used to analyze the bidirectional longitudinal association between time of screen exposure and internalizing and externalizing problems.ResultsA higher screen time exposure was significantly associated with the presence of internalizing and externalizing problems in children at T1 (3 years) (β = 0.62, SE = 0.29, p = 0.031; β = 0.79, SE = 0.25, p = 0.002). However, the association at T2 (5 years) was significant only for externalizing problems (β = 0.46, SE = 0.24, p = 0.054). The cross-lagged analysis revealed that externalizing problems at T1 significantly predicted higher screen time exposure at T2 (β = 0.08, SE = 0.04, p = 0.043), whereas higher screen time exposure at T1 did not significantly predict externalizing problems at T2 (β = −0.01, SE = 0.03, p = 0.71). No significant association in the crosslagged analysis was identified for internalizing problems.ConclusionThe results suggest an association between increased screen time and the development of internalizing and externalizing problems in Chilean children. Specifically, the results suggest that children who exhibit high levels of externalizing problems at a young age are more likely to spend more time on screens at an older age. This could be a form of coping mechanism, a result of parental behavior management strategies.